The Description of Psychological Aspect and Stigma Experienced by COVID-19 Survivors - Mira Utami Ningsih (Jurnal Keperawatan Terpadu (Integrated Nursing Journal), 2022)
COVID-19 cases continue to increase, in Mataram City, a total of 1093 was confirmed positive, 76 died, and 817 were declared cured. COVID-19 survivors are a group who have experienced not only physical, but also psychological discomfort. This research is a descriptive analytic study. The research sample is 46 people who are the COVID-19 survivors in the city of Mataram. The sample was selected by purposive sampling technique. The data collected are the psychological aspect including data on anxiety, stress and stigma experienced by COVID-19 survivors. The data were collected using a questionnaire and then analyzed descriptively and displayed in the frequency and percentage distribution table. The results showed a total of 74% of survivors experienced anxiety ranging from mild anxiety (33%), moderate (7%), severe (30%) and panic (4%). 100% of survivors experienced stress, including mild (59%), moderate (33%) and severe (7%) stress. On average, 13% of survivors are stigmatized about COVID-19. The stigma they get includes negative stereotypes, being labeled as carriers of infectious diseases, exclusion and discrimination. COVID-19 survivors are a group that needs help dealing with anxiety, stress and stigma. COVID-19 survivors and or other people with infectious diseases such as tuberculosis and HIV-AIDS should supported with psychological support. Various challenges including infectious diseases that may cause pandemics in the future, requiring us to prepare ourselves. Not only in terms of readiness in handling cases physically for recovery, but also from a social and psychological perspective of sufferers and society.